PERAN PASAR DISTRIBUTOR TERHADAP HARGA JUAL MINYAK GORENG - IIS NUR FAIZAH (Sahmiyya, 2022)
The market mechanism in general can be interpreted as a meeting place between sellers and buyers to carry out buying and selling transactions of goods and services. The market according to the study of economics has the meaning; The market is a place or condition that brings together demand (buyers) or supply (sellers) for each type of goods, services or resources. Buyers include consumers who need goods and services, while for industries need labor, capital and raw goods for production both to produce goods and services. The seller includes the industry offering the product or service requested by the buyer; workers sell their labor and skills, land owners rent or sell their assets, while capital owners offer to share profits from certain business activities. In general, all people or industries will play a dual role, namely as buyers and sellers. The type of research used by the researcher is descriptive qualitative, this type of research is suitable for use in this research because the descriptive qualitative analysis technique is analyzing, describing and summarizing various situation conditions from various data collected in the form of interviews or observations about the problems studied that occur in the field. The impact of the Covid 19 pandemic has affected the dynamics of the national food situation. The impact of restrictions on mobility through PSBB and other health protocols, encourages community activities to fulfill basic food needs to be limited. The implementation of PSBB is an obstacle for supply chain activities for basic and strategic food commodities so that retail prices generally increase